The reality of Talent Management of Emerging School Leaders in the Gneral Educational Directorates in the Sultanate of Oman - Al-Harthi, Khalsah; Al-Harthi , Aisha; Al-Ani, Wajeha (Jordan Journal of Educational Sciences, 2015)
This study aimed at exploring the reality of talent management of emerging school leaders in the General Educational Directorates in Sultanate of Oman and ways to improve it. Qualitative and quantitative approaches were used for data collection by using a questionnaire and semi-structured interviews. The questionnaire was applied to (400) supervisors in the Departments of Human Resources Development and the administrative staff in schools. The interviews were conducted with individuals holding positions of high leadership roles in the Omani Ministry of Education. The study found that the reality of talent management for emerging school leaders is below the desired level at the three levels investigated in the study: schools, departments of human resources development, and cooperation between the two. Qualitative data explained the reasons for this low level, and provided ways to improve it. The results also showed significant differences about the reality based on gender favoring females, and based on the nature of work favoring administrators in schools. The study recommended that a specialized job is established for talent management in the departments of human resources development. It also recommended the preparation of a second line of talented teachers to become school leaders in the future